Assessing the Impact of Mobile Applications on Student Engagement in ICT and Computer Science Education - Ibrahim, Umar (MultiTech Publisher, 2024)
This paper investigates the impact of mobile applications on student engagement in the realms of Information and Communication Technology (ICT) and Computer Science Education. As the integration of mobile applications in educational settings becomes increasingly prevalent, understanding their influence on student engagement is crucial for optimizing learning experiences. The study employs a [mention research design] to assess the effectiveness of selected mobile applications aligned with the curriculum. Data analysis involves [mention specific methods], focusing on measuring and evaluating student engagement levels. The results reveal [highlight key findings], shedding light on the implications for enhancing ICT and computer science education. This research contributes to the existing literature by addressing gaps and providing insights into the practical use of mobile applications in educational settings.